A Word Fitly Spoken - Maloney, Les D. (Peter Lang Inc., 2008)
A Word Fitly Spoken explores significant poetic devices within the four alphabetic acrostic psalms found in Book I of the Psalter. The majority of scholarly opinion has been that these acrostics are poetically and artistically deficient due to the writers’ and editors’ preoccupation with the alphabetic pattern. In contrast to this view, A Word Fitly Spoken proposes that the acrostic pattern contributes to, rather than detracts from, the poetic artistry of these psalms. In an effort to promote a holistic, canonical reading of the four acrostic poems within Book I of the Psalter, this study also examines the linguistic and grammatical connections within the text. Such a close reading repeatedly demonstrates the emotive power and the imagination of this literature in contradiction to its supposedly stiff, wooden nature. A Word Fitly Spoken is attuned to the frequent plays on word and sound that occur throughout these four poems and as such would be useful in graduate courses on biblical interpretation, Hebrew poetry, or the Psalms. «It is a new day in Psalms study, with significant contributions on canonical approaches and on Hebrew poetry. Les Maloney’s study centers on a close reading of the poetry of the acrostics in Book I of the Hebrew Psalter and so reflects the contemporary emphasis on the poetic dimension of the Psalms. Maloney argues for the poetic artistry of these psalms, a very different approach than that of previous scholarly generations. ‘A Word Fitly Spoken’ also raises the intriguing question of the placement of four alphabetic acrostics in Book I and four in Book V of the canonical Psalter. Those engaged in contemporary Psalms scholarship will find much to digest here.» (W. H. Bellinger, Jr., Chair, Department of Religion, W. Marshall and Lulie Craig Chairholder in Bible, Baylor University) «Les Maloney’s work on the acrostic psalms and the poetic figurations they contain should put to rest in their favor any debate on their artistic and theological value. Maloney has employed a critically informed imagination to demonstrate the significance of these fascinating psalms and how their literary features unfold their meanings in new and often surprising ways. I doubt that interested readers will ever read them again the same way.» (James M. Kennedy, Associate Professor of Religion, Baylor University)...
10.3726/978-1-4539-0389-6
Keywords: Akrostichon; Poetik